2022
DOI: 10.28991/cej-2022-08-02-07
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effect of Gradation, Temperature and Loading Duration on the Resilient Modulus of Asphalt Concrete

Abstract: This research was carried out to assess the effect of aggregate skeleton, temperature variation, and loading duration on the resilient modulus of asphalt concrete mixtures. Two different gradation methods, i.e., the conventional method of gradation and the Bailey method of gradation, were adopted to design the aggregate skeleton. The effect of these gradation methods, with temperature and loading duration, on the resilient modulus of asphalt concrete has not been previously investigated. The Modified Marshall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Figure 8 illustrates the increasing in the flexural strength with the rising in the percentage of steel shaving, as the corrugated and irregular shape of the lathe iron sheets provide higher strength for cohesion and bending after shedding the load compared to the plain mix, as stated by Junaid et al (35).…”
Section: Flexural Strengthmentioning
confidence: 82%
See 1 more Smart Citation
“…Figure 8 illustrates the increasing in the flexural strength with the rising in the percentage of steel shaving, as the corrugated and irregular shape of the lathe iron sheets provide higher strength for cohesion and bending after shedding the load compared to the plain mix, as stated by Junaid et al (35).…”
Section: Flexural Strengthmentioning
confidence: 82%
“…As the waste steel-to-volume ratio increased, the strength and ductility of the material also increased to some extent. In a previous study, the results showed that lathe residues significantly increase the strength, ductility and ultimate stress of concrete (35).…”
Section: Splitting Tensile Strengthmentioning
confidence: 88%
“…This is because there are cavities in the mixture [2][3][4]. Previous studies have been carried out to increase the compressive strength of porous paving, including using fly ash [5][6][7], using fiber [8,9], and using porous paving, whose compressive strength is inversely proportional to its permeability [4,10,11]. To maximize the function of porosity in porous concrete, Manan et al maximize the use of sand to increase the compressive strength of porous concrete [12].…”
Section: Introductionmentioning
confidence: 99%
“…This process is done by fixed crusher or mobility, as this process results in recycled aggregate and its use in various concrete mixtures. Several works used recycled materials to achieve the sustainability concept by using recycled concrete aggregate (RCA) and studied the behavior of concrete including the physical and chemical properties of fresh and hardened concrete [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%